Analisis Hubungan Antara Laba dan Tujuan Ekonomi Syariah Kontemporer - Choirunnisa, Wanda Hana; Noviyanti, Triana Ayu; Wigati, Sri (Maliyah : Jurnal Hukum Bisnis Islam, 2024)
This research discusses profits in Islamic economics by considering not only material aspects, but also spiritual aspects. In a sharia economic perspective, profits must take into account compliance with sharia principles such as the prohibition of usury, gharar and maysir. This study refers to the Al-Qur'an and Hadith to analyze the relationship between profit and economic goals in contemporary sharia business. The method used is qualitative research with a library research approach, which produces subjective conclusions. The aim of the research is to provide understanding to the public about the importance of following sharia economic principles in doing business. The formulation of the problem in this article is that many businesses in the 21st century still violate sharia principles, such as riba, gharar, and maysir. In this case thrifting contains elements that are not in accordance with sharia economic principles.